If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 6y = 13 + 6z Solving 3 + 6y = 13 + 6z Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 6y = 13 + -3 + 6z Combine like terms: 3 + -3 = 0 0 + 6y = 13 + -3 + 6z 6y = 13 + -3 + 6z Combine like terms: 13 + -3 = 10 6y = 10 + 6z Divide each side by '6'. y = 1.666666667 + z Simplifying y = 1.666666667 + z
| 83-4=8x+23 | | 3x-5=3+8-x | | 1/11y^-4 | | (4+3x)+x=36 | | -7/x+2=-4-3/x-3 | | xy+3x=2 | | 5ab+5c=10b-4ac | | -81=-(x-7)-15 | | 3x-5=(x+1) | | 5y+3-1xy=2x+8y-5 | | -7x+9=-40 | | (4_11/4:19/16).(_155/8)= | | 3x+9=-40 | | 87-2x=43x+22 | | 5(w-3)=w-11 | | P=3n | | 5p=6p+12 | | 62-3x=8x+15 | | 19a-7-17a+23=-14 | | 14=7x+4-5x | | 5x+9=58x-2 | | 5-0.03x=0.2-0.05x | | 2n-11+2n-11+n=18 | | 2-3m=m | | y=4x-31 | | 7x+10=8x+5 | | -6y+x=8 | | 15y-8-15y=17 | | -6x-5y=8 | | -3b=11 | | x-3/(x/4)-(4/x) | | x-3/((x/4)-(4/x)) |